Clinicopathological characteristics of desmoplastic ameloblastoma: A systematic review. Issue 1 (14th July 2017) - Anand, Rahul; Sarode, Gargi S.; Sarode, Sachin C.; Reddy, Mamatha; Unadkat, Hemant V.; Mushtaq, Shazia; Deshmukh, Revati; Choudhary, Shakira; Gupta, Nitin; Ganjre, Anjali P.; Patil, Shankargouda
Abstract: The aim of the present review was to systematically present the clinicopathological data of desmoplastic ameloblastoma (DA) from articles published in the literature. A comprehensive search of the databases (PubMed, Medline, SCOPUS, Web of Science, and Google Scholar) for published articles on DA was conducted. A total of 238 cases were identified and analyzed from 76 published papers. DA showed a slight male predilection (male: female=1.07:1) with a predominance in the fourth and fifth decades of life. Mandibular involvement (52.55%) was most commonly seen with a marked tendency for the anterior region (mandible: 40.9%, maxilla: 48.07%). The size of the lesion ranged from .5 cm to 20.4 cm, with the majority of cases measuring more than 3 cm in size (53.84%). Radiologically, most of the lesions presented mixed radiolucency and radiopacity (62%), and root resorption was observed in only seven cases. The majority of the lesions showed ill‐defined margins upon radiographic examination (65.78%). Most of the cases were treated with resection (78.57%), and five of the 10 recurrent cases were treated by enucleation/curettage. DA is characterized by the unique presentation of clinicopathological parameters. It is not possible to comment on its aggressive/recurrent nature and best treatment modality due to inadequate follow‐up data.